MAPK mutations and cigarette smoke promote the pathogenesis of pulmonary Langerhans cell histiocytosis - Huan Liu; Andrew R. Osterburg; Jennifer Flury; Zulma Swank; Dennis W. McGraw; Nishant Gupta; Kathryn A. Wikenheiser-Brokamp; Ashish Kumar; Abdellatif Tazi; Yoshikazu Inoue; Masaki Hirose; Francis X. McCormack; et al. (JCI Insight, 2020)
Pulmonary Langerhans cell histiocytosis (PLCH) is a rare smoking-related lung disease characterized by dendritic cell (DC) accumulation, bronchiolocentric nodule formation, and cystic lung remodeling. Approximately 50% of patients with PLCH harbor somatic BRAF-V600E mutations in cells of the myeloid/monocyte lineage. However, the rarity of the disease and lack of animal models have impeded the study of PLCH pathogenesis. Here, we establish a cigarette smoke–exposed (CS-exposed) BRAF-V600E–mutant mouse model that recapitulates many hallmark characteristics of PLCH. We show that CD11c-targeted expression of BRAF-V600E increases DC responsiveness to stimuli, including the chemokine CCL20, and that mutant cell accumulation in the lungs of CS-exposed mice is due to both increased cellular viability and enhanced recruitment. Moreover, we report that the chemokine CCL7 is secreted from DCs and human peripheral blood monocytes in a BRAF-V600E–dependent manner, suggesting a possible mechanism for recruitment of cells known to dominate PLCH lesions. Inflammatory lesions and airspace dilation in BRAF-V600E mice in response to CS are attenuated by transitioning animals to filtered air and treatment with a BRAF-V600E inhibitor, PLX4720. Collectively, this model provides mechanistic insights into the role of myelomonocytic cells and the BRAF-V600E mutation and CS exposure in PLCH pathogenesis and provides a platform to develop biomarkers and therapeutic targets.